A SURVEY OF PLANTS USED IN BASKET AND CORDAGE INDUSTRY BY THE TRIBALS AND INDIGENOUS PEOPLE OF INDO-NEPAL SUB HIMALAYAN TERAI REGION OF U.P. INDIA - Dixit, Dr Gopal; Vakshasya, Shilpa (Plantae Scientia, 2018)
The present manuscript covers different plants used in traditional cottage industry of rurals. In the present study of 15 plants of 8 Angiospermic families were reported after a number of randomly visits of various remote forest and rural areas of district Pilibhit. Plants parts used for making different articles like baskets, ropes, threads, bags, mats etc.were listed accordingly.